Occurrence of multiple mental health or substance use outcomes among bisexuals: a respondent-driven sampling study. (December 2016) - Bauer, Greta; Flanders, Corey; MacLeod, Melissa; Ross, Lori
Abstract Background Bisexual populations have higher prevalence of depression, anxiety, suicidality and substance use than heterosexuals, and often than gay men or lesbians. The co-occurrence of multiple outcomes has rarely been studied. Methods Data were collected from 405 bisexuals using respondent-driven sampling. Weighted analyses were conducted for 387 with outcome data. Multiple outcomes were defined as 3 or more of: depression, anxiety, suicide ideation, problematic alcohol use, or polysubstance use. Results Among bisexuals, 19.0 % had multiple outcomes. We did not find variation in raw frequency of multiple outcomes across sociodemographic variables (e.g. gender, age). After adjustment, gender and sexual orientation identity were associated, with transgender women and those identifying as bisexual only more likely to have multiple outcomes. Social equity factors had a strong impact in both crude and adjusted analysis: controlling for other factors, high mental health/substance use burden was associated with greater discrimination (prevalence risk ratio (PRR) = 5.71; 95 % CI: 2.08, 15.63) and lower education (PRR = 2.41; 95 % CI: 1.06, 5.49), while higher income-to-needs ratio was protective (PRR = 0.44; 0.20, 1.00). Conclusions Mental health and substance use outcomes with high prevalence among bisexuals frequently co-occurred. We find some support for the theory that these multiple outcomes represent a syndemic, defined as co-occurring and mutually reinforcing adverse outcomes driven by social inequity.